How Water Content Can Influence the Chemomechanical Properties and Physical Degradation under Aging of Experimental Adhesives - Stella Renata Machado Silva Esteves; Daphne Camara Barcellos; Tânia Mara da Silva; Mateus Rodrigues Silva; Tiago Moreira Bastos Campos; Elizabeth Pimentel Rosetti; César Rogério Pucci; Sérgio Eduardo de Paiva Gonçalves (Hindawi Limited, 2022)
Objective. To evaluate the physicochemical (sorption (SOR), solubility (SOL), and degree of conversion (DC)) and mechanical (flexural strength (FS), modulus of elasticity (ME), and compressive strength (CS)) properties of adhesives with different water contents (D2O). Materials and Methods. An adhesive was formulated: 55 wt% BisGMA, 45 wt% HEMA, 0.5 wt% camphorquinone, 0.5 wt% EDMAB, and 1.0 wt% DPIHP. D2O was added into the adhesives (0 wt%, 10 wt%, and 16 wt%). DC was monitored through the FTIR. FS, ME, CS, SOR, and SOL were tested. The adhesive samples were aged in deionized water, ethanol, and acetone. Data were submitted to ANOVA and Tukey's tests (5%). Results. For DC, the 0 wt% group showed a significant reduction (68.09 ± 0.14A) compared with the 10 wt% (87.07 ± 0.81B) and 16 wt% groups (89.87 ± 0.24B); 10 wt% showed the highest FS (MPa) mean values (141.6 ± 6.71B) compared with the 0 wt% (109.4 ± 20.5A) and 16 wt% (107.8 ± 15.8A). For the CS (MPa) and ME (GPa), the 16 wt% showed the lowest mean values (98.8 ± 18.0B and 2.2 ± 0.3B, respectively) compared with the 10 wt% and 0 wt%. For the SOR, 16 wt% of water showed the highest mean values and the ethanol showed the lowest mean values of SOL regardless of water content. Conclusion. The amount of water content and the types of aging solvents significantly affect the adhesive properties.